Eine lykische Opferformel - Diether SCHÜRR (Gephyra, 2021)
The tomb inscription TL 150 is terminated by a sacrifice formula. The addressee of the sacrifice seems to be the tomb builder itself, but ‚to sacrifice yearly‘ is probably dependent from zasãni, which should be a finite verb with the tomb builder as the indirect object. Xadrñna designates perhaps, what has to be sacrificed, but it may be instead a designation of the responsible person or even of the recipient(s) of the sacrifice. In each case the recipient(s) will be divine, as in TL 149 and 84, not the dead itself, as probably later in Greek inscriptions too.